2011
DOI: 10.1159/000331706
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Therapy for Asymptomatic Patients with Elevated Prostate-Specific Antigen: Can the Change in Prostate-Specific Antigen Reliably Guide Prostate Biopsy Decisions?

Abstract: Objectives: To assess the effects of a 4-week levofloxacin course on PSA in asymptomatic men with elevated prostate-specific antigen (PSA) and on prostate biopsy decision. Methods: Fifty asymptomatic men with elevated PSA (4.0–10.0 ng/dl) were given levofloxacin 500 mg/day for 4 weeks followed by repeat PSA. Prostate biopsy was recommended at the end of the study. We compared pre- and post-treatment PSA as well as PSA changes between prostate cancer cases and non-cancer patients. Results: Mean (±SD) PSA decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…(4) It was not differentiated whether GPs and ISs perform real population-based screening or a rather opportunistic PSA-based early PCa detection. (5) No conclusions could be extracted from our study neither concerning the type of counselling about advantages and disadvantages of PSA-based early PCa detection prior to PSA testing nor what kind of information sheets or similar material is used by GPs [23,24,25]. (6) Moreover, based on our study, we do not know how frequently GPs and ISs combine PSA testing with digital rectal examination as required by the German interdisciplinary S3 guideline for early detection of PCa [1].…”
Section: Discussionmentioning
confidence: 99%
“…(4) It was not differentiated whether GPs and ISs perform real population-based screening or a rather opportunistic PSA-based early PCa detection. (5) No conclusions could be extracted from our study neither concerning the type of counselling about advantages and disadvantages of PSA-based early PCa detection prior to PSA testing nor what kind of information sheets or similar material is used by GPs [23,24,25]. (6) Moreover, based on our study, we do not know how frequently GPs and ISs combine PSA testing with digital rectal examination as required by the German interdisciplinary S3 guideline for early detection of PCa [1].…”
Section: Discussionmentioning
confidence: 99%
“…PSA changes, however, were not significantly different between patients with prostate cancer and noncancer patients. Prostate cancer was detected in 20% of patients with a clinically relevant PSA decline [14]. An inflammatory pattern at primary biopsy is not associated with a decrease in prostate cancer incidence at repeated saturation prostate biopsy; therefore, only an accurate clinical evaluation including more parameters (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In a few studies that evaluating the histopathological results based on the PSA level changes obtained after antibiotherapy, it has been reported that there are no significant relations between the pathologic diagnoses and PSA levels as in this study for both cut off values (Dirim et al, 2009;Torky et al, 2011;Faydaci et al, 2012). On the other hand, it was found in the study of Serretta et al, (2008) that the rate of prostate cancer frequency in cases with PSA levels increasing or remaining unchanged following antibiotherapy was statistically higher as compared to those with decreasing PSA levels.…”
Section: Discussionmentioning
confidence: 42%
“…It has been reported that significant decreases in PSA levels can be seen following empirical use of antibiotics both in patients with chronic prostatitis and asymptomatic prostatitis (Schaeffer et al, 2005;Erol et al, 2006;Kaygısız et al, 2006;Serretta et al, 2008;Baltacı et al, 2009;Kyung et al, 2010;Stopiglia et al, 2010). In literature, there are some studies that significant decreases in PSA were observed following the antibiotherapy (Guercio et al, 2004;Kyung et al, 2010;Tang et al, 2010;Torky et al, 2011). In contrast, there are also studies reporting no significant PSA decreases Beside the studies reporting that there are no significant differences between the control PSA levels of cases who had received antibiotic therapy and the control PSA levels left to the natural course as reported in this study (Shtricker et al, 2009;Stopiglia et al, 2010;Heldwein et al, 2011;Eggener et al, 2013;Toktas et al, 2013;Fandella et al, 2014;Yang et al, 2015;Greiman et al, 2016), there are also contradicting studies (Erol et al, 2006;Saribacak et al, 2014;Topac et al, 2016).…”
Section: Discussionmentioning
confidence: 99%